(Re) pensando a contribuição dos centros de educação profissional do estado do Amapá, frente à inclusão laboral da pessoa com deficiência: análise curricular dos cursos de gestão. - SENA, Rita de Cássia Carvalho (2024)
The task of recruiting the professional who best fits the vacancy profile is a complex activity, even more so when it comes to protecting the world of work for minorities, a historic struggle for labor equality rights on the part of Persons with Disabilities - PwD. In this sense, it is important that human resources professionals, who are responsible for the functional movements of a company, leave their training knowing the normative principles of protecting PwD and with positive attitudes and inclusive methods that enable the understanding that including goes beyond meeting quotas. Within this context, the general objective of this research was to analyze the Pedagogical Political Projects of the technical courses in human resources at the Professional Education Centers of the State of Amapá, belonging to the Management axis, and to determine whether the curriculum of these courses complies with the guidelines provided for in laws, regarding content about people with disabilities, in their course plans and how this content promotes awareness about the labor inclusion of PwD. The results highlighted the need to rethink the curriculum of technical courses in Human Resources, só that it can equalize the real importance of inclusion in work environments. As a result of the didactic phenomenon of the research, a pedagogical course project (PPC) for Continuing Training of Teachers and management professionals is proposed as an educational product, aiming to strengthen integral human training in the conceptual framework of professional and Technological Education (EPT). Thus contributing to the training of future professionals who will deal with inclusive practices in the workplace.